Epidemiology and genetic diversity of soil-transmitted helminths and filaria of the genus Mansonella sp. at the human-nonhuman primate interface in Cameroon and Gabon - (:unkn) unknown (My University, 2021)
Non-human primates (NHP) are infected with many species of parasites ranging from protozoa to helminths. The high prevalence of certain parasitic infections in NHP may make these animals reservoirs of potentially zoonotic pathogens. Mansonella sp. are among the filariae that infect NHP, and M. perstans is widespread in sub-Saharan Africa where there is a large NHP population. Microscopic observation of blood samples is the standard method of diagnosis of M. perstans. However, one of the major obstacles in diagnosing blood-borne parasites in HNPs remains to obtain a blood sample. With evidence obtained in 2010 of the possibility of using feces to test for blood-borne parasites, we hypothesized that it would be possible to detect M. perstans DNA in the feces of NHP, but also that the presence of filarial DNA in feces would be associated with co-infections with Oesophagostomum sp., Necator sp. Many soil-transmitted helminths (STH) are shared between humans and NHP: notably Trichuris sp., Oesophagostomum sp., Ascaris lumbricoides, hookworms. In the second part of this thesis, we studied epidemiology and genetic diversity of these STH in wild NHP living in Cameroon and Gabon.We analyzed feces of NHP collected in Cameroon and Gabon for DNA of filaria of the genus Mansonella sp. and of STH: Trichuris sp., Oesophagostomum sp., Ascaris, and hookworms. We also analyzed sequences of M. perstans obtained from blood samples of patients suffering from mansonellosis in Cameroon. We obtained 121 sequences identical to the reference sequences of Onchocercidae. The cox1 sequences were grouped with the reference sequences of M. perstans, and those of Cameroonian patients carrying the filaria. The association between the presence of filarial DNA in feces and infection with Oesophagostomum sp. and Necator sp. was statically significant only in gorillas. Necator sp. infections were most common in gorillas, but were also present in chimpanzees, and one greater spot-nosed mon
Keywords: African Research